Are Eastern European agricultural markets working? Beware of state-prescribed market interventions! - Thomas Glauben; Ivan Djuric; Linde Götz; Ulrich Koester; Jens-Peter Loy; Zsombor Páll; Oleksandr Perekhozhuk; Sören Prehn; Swetlana Renner (Leibniz Institute of Agricultural Development in Central and Eastern Europe (IAMO), 2013)
Substantial danger exists that politically prescribed market interventions, designed to counter a supposed failure of the markets, will leave markets functioning worse rather than better. This is particularly true of Eastern European transition countries, where institutional regulations function only to a limited extent. Based on the findings of a variety of empirical studies that examine how Eastern European grain, dairy and meat markets are functioning, this policy brief strongly advocates restraint in the introduction of measures to regulate agricultural markets. Such regulations have high macroeconomic costs and may work counter to their objectives, which are designed to have popular appeal.
urn:nbn:de:gbv:3:2-32138
Keywords: 330